Pelatihan Keterampilan Kepemimpinan Digital Santri di Pondok Pesantren Riyadlusshorfi Wal Mantiq Pangandaran Provinsi Jawa Barat: Pengabdian - Baharuddin; Muthi, Ibnu; Khumaidi, Ahmad; Fitriah Eka Putri, Lailatul; Rosulinawati; Hilaliyah; Pandu Maulana, Muhamad; Ramadhan, Fajar; Dimyati, M.; Fahrun, Elva; Muntaha; Yuli Sugiarti, Diyah; Apriliantoni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The disruption of Industry 4.0 compels the education sector to adapt to digital technology, demanding digital leadership from school principals as drivers of transformation. However, challenges such as low digital literacy, limited infrastructure, and lack of motivation remain. This community service aims to equip students, teachers, and education staff with digital competencies to become agents of change in facing Society 5.0. The program was conducted through training/workshops led by expert speakers covering digital literacy and student innovation in the digital era. Participants engaged actively in discussions, Q&A sessions, and strategic planning exercises. Evaluation was carried out through direct observation and pre- and post-training questionnaires. Results showed that 85% of participants experienced significant improvement in knowledge and skills related to Islamic education planning. The training proved effective and strategic in preparing student leaders for the digital era with technology-based leadership competencies.